2017
DOI: 10.1002/ijc.30830
|View full text |Cite
|
Sign up to set email alerts
|

Tumor associated CD70 expression is involved in promoting tumor migration and macrophage infiltration in GBM

Abstract: Tumor migration/metastasis and immunosuppression are major obstacles in effective cancer therapy. Incidentally, these 2 hurdles usually coexist inside tumors, therefore making therapy significantly more complicated, as both oncogenic mechanisms must be addressed for successful therapeutic intervention. Our recent report highlights that the tumor expression of a TNF family member, CD70, is correlated with poor survival for primary gliomas. In this study, we investigated how CD70 expression by GBM affects the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…To determine the performance of this online tool, 53 previously published GBM prognostic factors collected as the procedure shown in Figure S1 and then they were evaluated in OSgbm (Table 2, Figure 1) (Sano et al, 1999;Hung and Howng, 2003;Heimberger et al, 2005;Aaberg-Jessen et al, 2009;Shirai et al, 2009;Pu et al, 2011;Cui et al, 2013;De Tayrac et al, 2013;Lee et al, 2013;Rosati et al, 2013;Wang et al, 2013;Wu et al, 2013;Bai et al, 2014;Han et al, 2014;Meng et al, 2014;Olmez et al, 2014;Zupancic et al, 2014;Maris et al, 2015;Moutal et al, 2015;Yan et al, 2015;Zhao et al, 2015;Chaurasia et al, 2016;Nduom et al, 2016;Steponaitis et al, 2016;Steponaitis et al, 2016;Zhang et al, 2016a;Zhang et al, 2016b;Deng et al, 2017;Dong et al, 2017;Ge et al, 2017;Han et al, 2017;Haynes et al, 2017;Huang et al, 2017;Li et al, 2017;Luo and Zhuang, 2017;Ma et al, 2017;Roy et al, 2017;Wu et al, 2017;Zhang et al, 2017;…”
Section: Validation Of Previously Reported Gbm Prognostic Biomarkersmentioning
confidence: 99%
“…To determine the performance of this online tool, 53 previously published GBM prognostic factors collected as the procedure shown in Figure S1 and then they were evaluated in OSgbm (Table 2, Figure 1) (Sano et al, 1999;Hung and Howng, 2003;Heimberger et al, 2005;Aaberg-Jessen et al, 2009;Shirai et al, 2009;Pu et al, 2011;Cui et al, 2013;De Tayrac et al, 2013;Lee et al, 2013;Rosati et al, 2013;Wang et al, 2013;Wu et al, 2013;Bai et al, 2014;Han et al, 2014;Meng et al, 2014;Olmez et al, 2014;Zupancic et al, 2014;Maris et al, 2015;Moutal et al, 2015;Yan et al, 2015;Zhao et al, 2015;Chaurasia et al, 2016;Nduom et al, 2016;Steponaitis et al, 2016;Steponaitis et al, 2016;Zhang et al, 2016a;Zhang et al, 2016b;Deng et al, 2017;Dong et al, 2017;Ge et al, 2017;Han et al, 2017;Haynes et al, 2017;Huang et al, 2017;Li et al, 2017;Luo and Zhuang, 2017;Ma et al, 2017;Roy et al, 2017;Wu et al, 2017;Zhang et al, 2017;…”
Section: Validation Of Previously Reported Gbm Prognostic Biomarkersmentioning
confidence: 99%
“…CD27, a costimulatory receptor of the TNF superfamily, is constitutively expressed on lymphocytes and hematopoietic stem/progenitor cells [44]. We found that CD27L is expressed on Lin − HLA-DR low CD11b + CD33 + MDSCs and the frequency of Lin − HLA-DR low CD11b + CD33 + CD27L + MDSCs is much higher in the BM than that in the peripheral blood of MDS patients [45].…”
Section: Innate Immune System In Mdsmentioning
confidence: 73%
“…Although we are the first to describe this effect by CD70-positive CAFs, CD70 overexpression on tumor cells has already been linked with migration in non-small cell lung cancer, melanoma and glioblastoma. [28][29][30] In the latter, knockdown of the CD70 gene resulted in a decrease in genes associated with tumor epithelial-mesenchymal transition (EMT) such as CD44 and SOX2. Also in CRC, overexpression of CD44 has been shown to drive EMT changes.…”
Section: Discussionmentioning
confidence: 99%